1995
DOI: 10.3109/09513599509160454
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic effect of GnRH agonist therapy on uterine leiomyoma vascularity

Abstract: The objective of this study was to correlate, during 12 weeks of therapy with gonadotropin releasing hormone agonist (GnRH-a), the chronological effect and the hemodynamic changes on the uterine artery and the leiomyometrial supplying vessels. Twenty-three premenopausal women with clinically diagnosed uterine leiomyomas received 3.75 mg of leuprolide acetate intramuscularly every 4 weeks for 12 weeks. Pretreatment values of serum estradiol, uterine and leiomyoma volumes and blood flow characteristics of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…This is consistent with prior reports that have demonstrated that estrogen and progesterone both promote angiogeneisis and growth factor production in female reproductive tissues (4,5) and that pelvic adhesions have estrogen and progesterone receptors (6). Additionally, estrogen deprivation causes an decrease in uterine blood flow, (7,8), and hypoestrogenism causes fibroids to shrink by approximately 40% after 3 months of GnRH-a therapy; thus, incision size would be expected to be smaller (8)(9)(10). Changes in the coagulation system, including plasminogen activator, plasminogen activator inhibitor, and matrix metalloproteinase, may also affect the mechanism of adhesion formation (11).…”
supporting
confidence: 91%
“…This is consistent with prior reports that have demonstrated that estrogen and progesterone both promote angiogeneisis and growth factor production in female reproductive tissues (4,5) and that pelvic adhesions have estrogen and progesterone receptors (6). Additionally, estrogen deprivation causes an decrease in uterine blood flow, (7,8), and hypoestrogenism causes fibroids to shrink by approximately 40% after 3 months of GnRH-a therapy; thus, incision size would be expected to be smaller (8)(9)(10). Changes in the coagulation system, including plasminogen activator, plasminogen activator inhibitor, and matrix metalloproteinase, may also affect the mechanism of adhesion formation (11).…”
supporting
confidence: 91%
“…Similar conclusions have also been reported by other authors [41,42,43]. In a prospective study using transvaginal color doppler sonography, Aleem et al [44] studied the hemodynamic effect of GnRH agonist therapy on uterine leiomyoma vascularity. The arterial resistance first increased in fibroid arteries in the fourth week of therapy.…”
Section: Gnrh Agonists: Application and Administration Effect On Fibrsupporting
confidence: 70%
“…A decrease in uterine blood flow was observed elsewhere in patients with leiomyomata during treatment with GnRH-a, and this effect has been proposed as an early mechanism leading to the reduction in leiomyoma and uterine volumes (32). Inhibitory effects on uterine blood flow in patients with leiomyomata were also described after treatment with the P antagonist mifepristone (33).…”
Section: Discussionmentioning
confidence: 95%